Examining the digital skills of nursing students: the power of information for problem-solving - Sari, Ni Putu Wulan Purnama; Artsanthia, Jintana; Marcello, Steven Aldo; Suvaree, Sudarat; Prachyakoon, Numpueng (Intelektual Pustaka Media Utama, 2024)
Our society is undergoing digital change. Dealing with digital technologies has become a daily practice. Many healthcare facilities are implementing digital technologies. Nurses are placed in a strategic position to be the leader of the digital healthcare workforce. Nursing students are more exposed to this technological advancement as they are future professional nurses. This study aimed to examine how information-processing and exchanging skills in digital spaces affect digital problem-solving skills among nursing students. The Bayesian mindsponge framework (BMF) was used as a conceptual framework. This quantitative study utilized a cross-sectional design. The population was all nursing students in two private nursing institutions located in Bangkok, Thailand (n=476) and Surabaya, Indonesia (n=179). Samples were the total population. Self-developed instrument was used in data collection. Data analysis used BMF analytics. The majority were females aged 20-22 years old who use smartphones and tablets daily. The information-processing and information-exchanging skills in digital spaces were positively associated with digital problem-solving skills among nursing students (MInformationProcess=0.30 and SDInformationProcess=0.05; MInformationExchange=0.37, and SDInformationExchange=0.05). More efforts are needed to improve nursing students’ problem-solving skills by using digital content, for instance, by modifying the information-processing and information-exchanging skills in digital spaces. Collaborative learning methods should be promoted in order to support the creation of conducive environment for supporting knowledge or information-exchanging behavior among nursing students by using digital technology.